Usefulness of Intraoperative Infrared Thermography in Intracranial Surgeries: Past, Present, and Future - Camila Monteiro Gonçalves da Costa; Vinícius Verbicário Botelho da Costa; Caio Araujo de Souza; Diego Rodrigues Menezes; Marcus Andre Acioly (Brazilian Neurosurgery, 2024)
With the advancement of technology in Neurosurgery, imaging guidance for surgical planning and intraoperative assessment has become relevant. Currently, two major methods of imaging guidance are generally explored in the literature, namely based on imaging and fluorescence. These techniques, however, are not without limitations. Thermal imaging has potentially broad applications in clinical practice, especially for intracranial diseases. Infrared thermography (IT) has been an underestimated tool with few reports on its usefulness during intracranial surgeries. In this article, we aim to provide a brief discussion on the limitations of current intraoperative imaging techniques for intracranial surgeries and to provide an in-depth state-of-the-art review on intraoperative IT (IIT) for intracranial lesions. High-resolution IIT is a non-invasive alternative imaging method that provides real-time estimation of regional cerebral blood flow. For brain tumors, the studies were mostly directed to diagnostic purposes and occasionally for lesion-localization. The use of IIT to address the extent of resection is a potential new application. Clinical data in this issue suggests that IIT might detect residual tumors, occasionally not assessed by other imaging technologies. Thermographic measurements during vascular and epilepsy surgeries comprise an interesting field for future research with potential clinical implications. Further experimental and clinical studies should be addressed to provide technical refinements and verify the usefulness of this noninvasive technology in neurosurgery.